Effects of Smartphone Use on Sleep Quality, Depression, Anxiety, and Academic Achievement - Megawati, Eka Roina; Wijaya, Fransiska Oktavia (Jurnal Kesehatan Masyarakat, 2023)
Smartphones are popular devices that can process a lot of information than standard cell phones.  The easier access to the internet due to the increased of smartphone technology is followed by the increase of the prevalence of smartphone users. There are several adverse effects due to the smartphone use such as physiological, psychological, social, and emotional disturbances. These adverse effects depend on the duration and frequency of smartphone use. The aim of this study was to determine the effect of smartphone use on sleep quality, depression, anxiety, and academic achievement on students. This is an observational analytic study with a cross-sectional design. The subjects of this study were 100 students that were given questionnaire about smartphone use with Smartphone Addiction Scale-Short Version (SAS-SV), sleep quality with Pittsburgh Sleep Quality Index, depression anxiety using DASS21, and academic achievement. The data was analyzed by using Spearman rho analysis. This study found significant relationship of smartphone use to sleep quality, depression anxiety with p value 0.027 and 0.001 respectively, but there was no significant relationship of smartphone use and academic achievement (p value = 0.182).